2009
DOI: 10.1111/j.1365-2982.2009.01336.x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of intramuscular and submuscular interstitial cells of Cajal and associated enteric nerves is related to decreased gastric emptying in streptozotocin‐induced diabetes

Abstract: Interstitial cells of Cajal (ICC) are associated with afferent innervation and peristalsis of the stomach suggestive of a key role in the pathophysiology of gastroparesis. We studied changes in the density and ultrastructure of ICC and enteric nerves in the streptozotocin-induced diabetes mellitus (STZ-DM) in Wistar rats using immunohistochemistry and electron microscopy. Gastric emptying was studied in vivo by single-photon emission computed tomography. In the STZ-DM antrum, a marked reduction was observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 63 publications
(87 reference statements)
5
86
2
1
Order By: Relevance
“…As pointed out by Wang et al, an older study in dogs demonstrated antral contractile forces open the pylorus [13,14]. The current study finding of reduced antral smooth muscle ICC in both GP and GLS cannot be extrapolated to support this finding.…”
Section: Interstitial Cells Of Cajalcontrasting
confidence: 39%
“…As pointed out by Wang et al, an older study in dogs demonstrated antral contractile forces open the pylorus [13,14]. The current study finding of reduced antral smooth muscle ICC in both GP and GLS cannot be extrapolated to support this finding.…”
Section: Interstitial Cells Of Cajalcontrasting
confidence: 39%
“…27 Similar to changes observed with electroacupuncture, 24,25 mRNA expression of KIT in the stomach tissue was increased after treatment with Curcumin, the main active component of the spice turmeric. 27 Wang et al 28 reported that the density of ICC-IM and ICC-SM was reduced by 46.4% and 26.7%, respectively in the antrum of streptozotocin induced diabetic rats. In addition, Long et al 29 showed depleted antral ICC and ultrastructural changes such as decreased number of gap junctions of ICC in the antrum and damaged ICC organelles of the diabetic rats.…”
Section: Gastroparesis and Interstitial Cells Of Cajal In Animal Modelsmentioning
confidence: 99%
“…ICC are associated with afferent innervation and peristalsis of the stomach suggestive of a key role in the pathophysiology of gastroparesis. Recently study was investigated that changes in the density and ultrastructure of ICC and enteric nerves in the streptozotocininduced diabetes mellitus (STZ-DM) in Wistar rats using immunohistochemistry and electron microscopy (Wang et al, 2009). In the STZ-DM antrum, a marked reduction was observed in the density of the intramuscular ICC (ICC-IM) and ICC located at the submucosal border of the circular muscle layer of the antrum (ICC-SM).…”
Section: Pathophysiology Of Icc In Diabetic Gastroparesismentioning
confidence: 99%